Algebra Tiles as Physical Manipulatives to Support Students’ Understanding of Linear Equations in One Variable - Dyah Sinto Rini (SEAMEO Regional Centre for QITEP in Mathematics, 2022)
To help students in solving the linear equations in one variable, teacher can use a learning media such as algebra tiles. Algebra tiles are square and rectangle-shaped tiles that represent numbers and variables. Algebra tiles consist of three different-size pieces. The smallest tile is square shape and represents ± 1, the other tile is rectangular shape and represents ± x and the largest tile is large square shape that represents ± x2. The pieces are usually colour-coded so that one colour represents positive values and another color represents negative values. This research is a best practice that was conducted at class VII.7 SMPN 18 Tangerang. The aim of this research is to describe how the algebra tiles supports students’ understanding in solving linear equations in one variable. The competence achievement indicators are: modelling algebraic expressions using algebra tiles; solving linear equations in one variable using algebra tiles; solving linear equations in one variable without use algebra tiles. Data collection through photos, videos, worksheet and students’ work. Students did reducing and balancing ways to find the simple form of algebra tiles. The purpose of reducing or balancing of both sides of linear equations in one variable is to get how many square tiles that equals to one rectangular tile. Algebra tiles made students to be easier in solving linear equations in one variable. Students were very happy to learn mathematics using algebra tiles. The algebra tiles supports students’ understanding in solving linear equations in one variable.